Inflammatory diseases of blood vessels - Hoffman, Gary S., 1942- (Wiley-Blackwell, 2012)
"In recent years, considerable progress has been made in understanding the vasculitic diseases, largely due to the introduction of effective treatments for diseases that were once uniformly fatal, the conduct of structured clinical studies, and advances in immunology and molecular biology. Despite these achievements, the vasculitic diseases continue to be associated with morbidity and mortality from chronic organ damage, relapses, and the side effects of treatment. Investigations into the mechanisms of vascular inflammation may lead to a better comprehension of the pathogenesis of vasculitic diseases and to treatment that is more effective and less toxic. These areas of promising research, together with current knowledge about the vasculitic diseases, are extensively examined in this new edition, which is designed to provide a comprehensive overview of the science and clinical consequences of vascular inflammation in health and disease"--Provided by publisher.